Cigarette smoke promotes inflammasome‐independent activation of caspase‐1 and ‐4 leading to gasdermin D cleavage in human macrophages. Issue 9 (25th August 2022) - Buscetta, Marco; Cristaldi, Marta; Cimino, Maura; La Mensa, Agnese; Dino, Paola; Bucchieri, Fabio; Rappa, Francesca; Amato, Santina; Aronica, Tommaso Silvano; Pace, Elisabetta; Bertani, Alessandro; Cipollina, Chiara
Abstract: Mechanisms and consequences of gasdermin D (GSDMD) activation in cigarette smoke (CS)‐associated inflammation and lung disease are unknown. GSDMD is a downstream effector of caspase‐1, ‐8, and ‐4. Upon cleavage, GSDMD generates pores into cell membranes. Different degrees of GSDMD activation are associated with a range of physiological outputs ranging from cell hyperactivation to pyroptosis. We have previously reported that in human monocyte‐derived macrophages CS extract (CSE) inhibits the NLRP3 inflammasome and shifts the response to lipopolysaccharide (LPS) towards the TLR4‐TRIF axis leading to activation of caspase‐8, which, in turn, activates caspase‐1. In the present work, we investigated whether other ASC‐dependent inflammasomes could be involved in caspase activation by CSE and whether caspase activation led to GSDMD cleavage and other downstream effects. Presented results demonstrate that CSE promoted ASC‐independent activation of caspase‐1 leading to GSDMD cleavage and increased cell permeability, in the absence of cell death. GSDMD cleavage was strongly enhanced upon stimulation with LPS+CSE, suggesting a synergistic effect between the two stimuli. Noteworthy, CSE promoted LPS internalization leading to caspase‐4 activation, thus contributing to increased GSDMD cleavage. Caspase‐dependent GSDMD cleavage was associated with mitochondrial superoxide generation. Increased cleaved GSDMD was found in lung macrophages of smokers compared to ex‐smokers and non‐smoking controls. Our findings revealed that ASC‐independent activation of caspase‐1, ‐4, and ‐8 and GSDMD cleavage upon exposure to CS may contribute to macrophage dysfunction and feed the chronic inflammation observed in the smokers' lung.